Health promotion interventions in type 2 diabetes - Monica Sørensen; Henny-Kristine; Marina Maggini; Silke Kuske; Andrea Icks; Ulrike Rothe; Jaana Lindström; Jelka Zaletel (Istituto Superiore di Sanità, 2015)
AIM. To present the most common quality criteria in health promotion interventions in type 2 diabetes mellitus (T2DM). METHODS. A systematic literature search was conducted to identify review articles, health technology assessments and policy reports of evaluated health promotion interventions in T2DM. A descriptive analysis of study characteristics and evaluation criteria are presented. RESULTS. Seven studies met the inclusion criteria. The findings indicate that the most common health promotion interventions used in T2DM are initiatives targeting health care professionals. The main ambition of the programs was to increase the collaboration between health care professionals and patients, and between health care centres, program managers and community stakeholders. CONCLUSIONS. This investigation extends our knowledge of the most common health promotion interventions in T2DM and which structure, process and outcome measurements that are reported in such interventions. Future research could usefully explore how the effectiveness of multicomponent and complex interventions may be evaluated and extend the association of these factors into other settings and in relation to other lifestyle related chronic diseases.